Transcriptomic analysis of adhesive capsulitis of the shoulder. Issue 10 (17th April 2020) - Kamal, Nima; McGee, Sean L.; Eng, Kevin; Brown, Graeme; Beattie, Sally; Collier, Fiona; Gill, Stephen; Page, Richard S.
Abstract: Adhesive capsulitis (AC) is a disabling condition of the shoulder joint affecting 2 to 5% of the general population. Our understanding of the molecular mechanisms is limited. The present study aimed to determine potential biomarkers of AC through transcriptomic analysis. This multi‐centre study investigated patients undergoing arthroscopic capsulotomy surgery for resistant AC compared to those undergoing arthroscopic stabilization surgery for glenohumeral instability (control). Tissue samples were harvested from the anterior capsule during surgery. Total RNA was extracted and RNA‐sequencing‐based transcriptomics were performed. A number of genes deemed differentially expressed in RNA‐sequencing analysis were validated using real‐time reverse transcription polymerase chain reaction (RT‐PCR). Baseline characteristics of the AC group (n = 22) were; mean age 52.7 years (SD: 10.2), 73% female, and Oxford Shoulder Score 19.6 (SD: 8.0), compared with the control group (n = 26), average age 23.9 years (SD: 5.2), 15% female, and Oxford Shoulder Score 39.0 (SD: 7.4). Transcriptomic analysis with false discovery rate correction and log2 fold change cut‐off of ±1.5 revealed 545 differentially expressed genes in AC relative to control. Bioinformatic analyses were carried out to identify biological processes and pathways enriched in this dataset. Real‐time RT‐PCR using two different normalization processes confirmed increased expression of matrix metallopeptidase 13 ( MMP13 ) and platelet‐derived growth factor subunit B ( PDGFB ), in patients with AC, while tumor necrosis factor α ( TNFA ) expression was reduced. These findings provide a comprehensive assessment of transcriptional changes associated with AC that give insights into the aetiology of the disease and provides a resource for molecular targets to better diagnose and treat this condition.